2019
DOI: 10.3390/pharmaceutics11090464
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Safety Profile of a Single-Stranded RNA Nano-Structure Adjuvant

Abstract: Adjuvants enhance the efficacy of vaccines by stimulating immune response-related gene expression and pathways. Although some adjuvants have been approved for commercial use in human vaccines (e.g., Alum, MF59, and AS03), they might elicit adverse side effects, such as autoimmune diseases. Recently, we developed a novel single-stranded RNA (ssRNA) nano-structure adjuvant, which can stimulate both Th1 and Th2 responses. In this study, we evaluated the safety and toxicological profiles of this ssRNA nano-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
(103 reference statements)
2
11
0
Order By: Relevance
“…42,43 A previous study established that ssRNA adjuvants are relatively safe. 44 Taken together, these results verify that the gE protein produced in this study can be a new VZV protein vaccine candidate. Moreover, the ssRNA derived from CrPV IGR IRES encoding the gE gene, which could express gE in transfected cells, can effectively function as a vaccine adjuvant in a protein-based subunit vaccine by activating humoral and cell-mediated immune responses.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…42,43 A previous study established that ssRNA adjuvants are relatively safe. 44 Taken together, these results verify that the gE protein produced in this study can be a new VZV protein vaccine candidate. Moreover, the ssRNA derived from CrPV IGR IRES encoding the gE gene, which could express gE in transfected cells, can effectively function as a vaccine adjuvant in a protein-based subunit vaccine by activating humoral and cell-mediated immune responses.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, the mode of action of AddaVax has not yet been elucidated 42,43 . A previous study established that ssRNA adjuvants are relatively safe 44 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, side effects such as autoimmune/inflammatory syndrome induced by adjuvants also occur, requiring further confirmation of safety [30,31]. To compensate for these limitations, RNA adjuvants have recently been developed [19] and applied to MERS and influenza, as they did not accumulate in the body, thus lowering the risk of side effects and effectively increasing the immune response [17,18]. We found that immunization with MERS S protein with RNA adjuvant and alum synergistically induced the humoral immune response and led to balanced Th1/Th2 responses [17].…”
Section: Discussionmentioning
confidence: 99%
“…11 ) [ 89 , 90 ]. Some atypical vaccine adjuvant materials, such as polymers, RNA, polysaccharides and carbon dots, are currently available, which will not be described one by one [ [91] , [92] , [93] , [94] , [95] ]. Their physicochemical surface properties, self-assembly and aggregation, and the interaction with biological molecules will influence their immune behavior, toxicities and biological effects [ [96] , [97] , [98] , [99] , [100] ].…”
Section: Nanoparticles As Vaccine Adjuvants In Antiviral Infectionmentioning
confidence: 99%